1971
DOI: 10.1136/bmj.4.5784.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormonal Therapy on Plasma Testosterone Levels in Prostatic Carcinoma

Abstract: SummaryPlasma concentrations of testosterone were estimated in normal men, in patients before treatment for prostatic cancer, and in patients who had had various forms of endocrine treatment for prostatic carcinoma. There was no decline in plasma testosterone levels with age. Patients with non-metastatic disease had levels similar to those of normal controls, but in advanced metastaticdisease the levels were low. After orchidectomy the plasma testosterone level fell to that found in normal women. In every pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
2

Year Published

1972
1972
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(53 citation statements)
references
References 14 publications
(9 reference statements)
3
47
1
2
Order By: Relevance
“…The prostatic tumor enlarged somewhat, and there were no visible improve ments in such subjective symptoms as dysuria. Robinson and Thomas (1971). The differences between our findings.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The prostatic tumor enlarged somewhat, and there were no visible improve ments in such subjective symptoms as dysuria. Robinson and Thomas (1971). The differences between our findings.…”
Section: Discussioncontrasting
confidence: 49%
“…As a result, they found that each treatment caused a marked fall in the level of plasma testosterone, irrespective of the clinical response. Robinson and Thomas (1971) noted that in prostatic cancer patients, the administration of stilbestrol at a daily dose of only 3 mg could reduce the plasma testosterone level to as low as 10 ng/100 ml or less, a result which was almost equivalent to the effects of larger dosage, 100 mg per day. Commenting on this conspicuous fall in the level of plasma testosterone, which even dipped below female levels, they reasoned that stilbestrol may directly inhibit the production of androgens in the adrenal cortex, exemplified by the fact that the level of testosterone fell more markedly in orchidectomized patients who underwent additional hormonal therapy with stilbestrol than in those who did not.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Reduction of circulating testosterone from the normal range of 3-6ngml-' of serum (= I x 10-8 M-2 X 10-8M) to about 0.3 ng ml' (= 1 x 10-9 M) by surgical or to about 0.06 ng ml-' (= 2 x 10-0 M) by medical castration (Robinson & Thomas, 1971) leads to at least partial remission of androgen-dependent cancers. Growth properties of LNCaP cells characterised in this report and by others refute the hypothesis of androgen dependence of this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…La supresión persistente de T tras la administración de estrógenos ha sido observada por otros estudios [22][23][24] . En el caso de supresión androgénica mediante análogos LH-RH la posibilidad de hipogonadismo muy prolongado ya fue seña-lado por Stevens 25 que observa que durante 12 meses los pacientes presentaban síntomas de hipogonadismo y ya entonces advertía de que la acción exclusivamente aguda de los análogos LH-RH no se cumplía siempre.…”
Section: Edadunclassified